Late-Life Decline in Well-Being across Adulthood in Germany, the UK, and the US: Something Is Seriously Wrong at the End of Life - Denis Gerstorf; Nilam Ram; Guy Mayraz; Mira Hidajat; Ulman Lindenberger; Gert G. Wagner; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Throughout adulthood and old age, levels of well-being appear to remain relatively stable. However, evidence is emerging that late in life well-being declines considerably. Using long-term longitudinal data of deceased participants in national samples from Germany, the UK, and the US, we examine how long this period lasts. In all three nations and across the adult age range, well-being was relatively stable over age, but declined rapidly with impending death. Articulating notions of terminal decline associated with impending death, we identified prototypical transition points in each study between three and five years prior to death, after which normative rates of decline steepened by a factor of three or more. The findings suggest that mortality-related mechanisms drive late-life changes in well-being and highlight the need for further refinement of psychological concepts about how and when late-life declines in psychosocial functioning prototypically begin.
Keywords: 330; Selective mortality; successful aging; differential aging; psychosocial factors; well-being; multiphase growth model; Alternde Bevölkerung; Lebensqualität; Soziale Lage; Alterskrankheit; Sterblichkeit; Gerontologie; Deutschland; Großbritannien; USA